Desenvolvimento de indicadores de consumo de materiais e de custo de diferentes metodologias para combater a flutuabilidade de dutos enterrados - Lenz, Ricardo Luis (Universidade do Vale do Rio dos Sinos, 2019)
Pipeline transportation, mainly used to carry gases and liquids, is one of the most important modes, even though it’s not used much in Brazil, with a short participation of 4,4% in the transport matrix. Despite the high initial investment for its construction, given the complexity of this mode of transport, it has low maintenance costs, operation and environmental impacts during its lifetime when compared to different modals. This study aims to compare alternatives of systems to control the buoyancy of pipelines, in terms of resources and costs, analysing the logistics of material transport, execution of the construction phases impacted by the systems and application materials. The research was conducted following 4 steps, which are the (1) definition of appropriate and unsuitable conditions for the three building systems; (2) definition of a scenario where it’s possible to place the three different systems; (3) analysis of the systems building process; and (4) definition of the cost and material consumption for each system, with pipe diameter variation. The results indicated gains in the use of manpower and equipment resources when using geotextile and tie rods, as well as logistics and productivity gains, besides its application occurs at the end of the construction process. However, the high cost of geotextile, given that it’s an imported material, increased the final cost of this methodology, specially in large pipe diameters. In conclusion, taking into account both cost and use of materials, the use of tie rods presented advantages when compared to traditional options such as concrete jacketing and geotextile.
Keywords: Indicadores de consumo de recursos; Indicadores de custo; Sistemas de combate à flutuabilidade de dutos; Resource consumption indicators; Cost indicators; Pipeline buoyancy prevention systems; ACCNPQ::Engenharias::Engenharia Civil